Spatial Variation in General Medical Services Income in Dublin General Practitioners - O'DOWD, THOMAS; KELLY, ALAN (My University, 2011)
The general medical services (GMS) scheme provides care free at the point of use for the 30% most economically deprived section of the population and the elderly. Almost all people of over-70-year olds are eligible for the GMS scheme potentially directing resources away from those most in need. The aim of this study is to analyse the relationship between practice GMS income and deprivation amongst Dublin-based general practitioners (GPs). The practice GMS income in Dublin was analysed in relation to practice characteristics including the number of GPs, catchment area population, proportion of over-70-year olds in the catchment area, catchment deprivation, number of GMS GPs within 2?km, and average GMS practice income within 2?km. Practice GMS income was highest in deprived areas but is also a valuable source of income in the least deprived areas. The capitation rate for over-70-year olds provides an incentive for GPs to locate in affluent areas and potentially directs resources away from those in greater need.
PUBLISHED
Keywords: Public Health; General Practitioners; Ireland; general medical services (GMS) scheme